MENINGKATKAN KUALITAS BAHASA INDONESIA MELALUI BAHASA INDONESIA HUKUM ILMIAH - Dheni Harmaen (Fakultas Hukum Universitas Pasundan, 2014)
Legal language is not the language that stands alone, but rather a special Indonesian which applied to the field of law. Statutory language should not leave the rules that apply in Indonesian, both on sentence structure, word origin, meaning and other rules applicable in Indonesian. Conceptual mindset is a practical theory in making a scientific essay, of course, the legal language also have characteristics in accordance with the characters contained in the legal science itself, in some instances the use of legal language different from the general Indonesian language, but the difference is merely casuistry, including the use of language in other scientific, it can be seen from the use of the word which is only valid for a certain science that we call functional language or profession languages. The diversity of Indonesian law in terms of linguistics is a meta language that is diverse results of the study or product of human thought which is not limited to just one language, but also involves other scientific. In light of the language of law, Indonesian law is the primary means for carrying out their profession, so the language professions have different features from a variety of common language. Keywords: Language; Law; Function; Profession.